2013
DOI: 10.1097/iop.0b013e3182805a4f
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Punctal Occlusion Using Pigtail Probe

Abstract: Punctoplasty using the pigtail probe seems to be a safe and effective method for identifying and repairing occluded puncta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Knapp et al compared deep and superficial lacrimal puncta cauterization and found out that, punctum remained close in deeper thermal cautery more significantly [44].Nevertheless, the occluding procedure may be either overused or underused, sometimes permanent or congenital occluding should be reopen using a pigtail probe to prevent symptoms such as epiphora [45].…”
Section: Discussionmentioning
confidence: 99%
“…Knapp et al compared deep and superficial lacrimal puncta cauterization and found out that, punctum remained close in deeper thermal cautery more significantly [44].Nevertheless, the occluding procedure may be either overused or underused, sometimes permanent or congenital occluding should be reopen using a pigtail probe to prevent symptoms such as epiphora [45].…”
Section: Discussionmentioning
confidence: 99%
“…A pitfall of the current study is that our technique is not applicable in case of a partial or complete occlusion of nasolacrimal duct. A case series on 5 cases with punctal occlusion used the pigtail probe to locate and incise the occluded punctum [13]. However, they used the classic lacrimal tube to maintain patency and prevent reocclusion of the lacrimal passages.…”
Section: Discussionmentioning
confidence: 99%
“…The pigtail probe has generally been used for treatment of canaliculus lacerations [11, 12]. Recently, it was used to detect the site of the occluded punctum in a small case series and proved effective [13].…”
Section: Introductionmentioning
confidence: 99%